Head Tilting Elicited by Head Turning in Three Dogs with Hypoplastic Cerebellar Nodulus and Ventral Uvula - Tamura, Shinji; Nakamoto, Yuya; Uemura, Takashi; Tamura, Yumiko (Frontiers in Veterinary Science, 2016)
The nodulus and ventral uvula (NU) of the cerebellum play a major role in vestibular function in humans and experimental animals; however, there is almost no information about NU function in the veterinary clinical literature. In this report, we describe three canine cases diagnosed with presumptive NU hypoplasia. Of them, one adult dog presented with cervical intervertebral disk disease, and two juvenile dogs presented with signs of central vestibular disease. Interestingly, an unusual and possibly overlooked neurological sign that we called “positioning head tilt” was observed in these dogs. The dogs were able to turn freely in any direction at will. The head was in a level position when static or when the dog walked in a straight line. However, the head was tilted to the opposite side when the dog turned. Veterinary clinicians should be aware of this neurological sign, which has not been reported previously, and its application in lesion localization in dogs.